Mekanisme Pengendalian Emosi dalam Bimbingan dan Konseling - Akhmad Syah Roni Amanullah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2022)
This study contains a discussion of the mechanisms and techniques that can be done by someone including students to practice controlling their emotions taken from various counseling approaches, both Islamic and Western, which are found in various scientific literature. The purpose of this study is to find out theoretically that in psychology books and guidance and counseling as well as articles on guidance and counseling there are various mechanisms of emotional control both in terms of behavioral counseling, reality counseling, cognitive counseling and Islamic counseling that can be read, understood, internalized and implemented. in daily life so that a person can become a wise person every time he takes steps in behavior and in responding to various kinds of life conditions. The method in this research is the literature review method. Researchers conducted a literature study of various books and scientific works that discussed emotional control and counseling guidance from both general and Islamic science reviews. The results of the study stated that there are six mechanisms of emotional control that can be applied by anyone, including students at school. The six mechanisms are; (1) emotion control mechanism using displacement technique. (2) the mechanism of emotional control by using cognitive adjustment techniques. (3) emotion control mechanism using self talk technique (4) emotion control mechanism using ablution technique (5) emotion control mechanism using deep breathing technique and (6) emotion control mechanism using coping technique. The conclusion of this research is that there are many ways, many techniques and mechanisms that can be used by someone to serve as a way of controlling emotions. The six mechanisms are relatively successful techniques in helping a person to practice controlling his emotions.